HUBUNGAN PENGETAHUAN DAN SIKAP IBU DENGAN PEMBERIAN ASI EKSLUSIF DI PUSKESMAS SILAU LAUT, KEC. SILAU LAUT KAB. ASAHAN TAHUN 2024 - Hadi, Tifani (Universitas Haji Sumatera Utara, 2025)
Breast milk offers many benefits, including reducing the risk of infectious diseases and preventing non-infectious conditions like allergies, obesity, malnutrition, asthma, and eczema. Additionally, it can improve a child’s intelligence quotient (IQ) and emotional quotient (EQ). This study aims to analyze the relationship between mothers' knowledge and attitudes towards exclusive breastfeeding at the Silau Laut Public Health Center, Silau Laut Subdistrict, Asahan Regency, in 2024. The study used an analytical survey with a cross-sectional design. The population consisted of 38 pregnant women at the health center, and a sample of 30 participants was selected using the total sampling technique. Data were analyzed using the chi-square test. The findings showed that most mothers had good knowledge (20 participants or 52.6%) and positive attitudes (20 participants or 52.6%) towards exclusive breastfeeding. The chi-square test indicated a significant relationship between mothers' knowledge and exclusive breastfeeding (P-value = 0.002 < 0.05) and between mothers' attitudes and exclusive breastfeeding (P-value = 0.005 < 0.05). The study concludes that there is a significant relationship between mothers' knowledge and attitudes and the practice of exclusive breastfeeding. It is recommended that mothers actively seek information to enhance their understanding of the benefits of exclusive breastfeeding.